Mediokrasi: Tantangan Bagi Pelayanan Kristen - Zeffry Zeffry; Hidradjat Juliana (Jurnal Syntax Admiration, 2025)
Mediocratis is a social system in which individuals with average or substandard abilities hold positions of power or influence, ignoring the qualities or competencies that should be possessed to hold those positions. In daily life, both work, association and the context of Christian ministry, mediocracy is a challenge that must be seriously addressed because the dynamics of church life are developing rapidly. There are many people who choose to be mediocre when most of them are competent people, have a lot of talent and opportunities to advance or develop.